ANALISIS BIAYA PRODUKSI PENAMBANGAN BATU KAPUR PADA BULAN APRIL 2017 DI BUKIT KARANG PUTIH PT. SEMEN PADANG - Elsa Rahma Afrila; Sumarya Sumarya; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2018)
PT Semen Padang is planning to increasing production of limestone of 650,749 tons from actual production 580.17 ton. Increased production of limestone will cause an increasing the cost of production, so the planning of main cost production of limestones per ton from the mining location to the hauling front to a dumping area is required. This cost of production was determined by how much mechanical equipments used from mining front to the dumping area. Afterwards, the cost is also influeced by the depth of the explosive holes. The depth of explosive holes should be customized by the target production from the company.Productivity of drilling machine Furukawa HCR 1500-ED II is 1.519,86 ton/hour. Productivity of loader digging equipment Backhoe Caterpillar 6030 (EC-03) is 1.292,37 tons/hour. Productivity of hauling equipment Dumptruck Komatsu HD 785-7 is427,62 tons/hour, so to reach the production target 650,749 ton is required 1 unit of drilling machine Furukawa HCR 1500 – ED II, 1 unit of Backhoe Caterpillar 6030 (EC-03), and 3 units of Dumptruck Komatsu HD 785-7. An appropriate from the depth of explosive holes to achive production target is 8.999,43 m. Production cost per ton of limestone from the mining front to the dumping area that must be issued by company in April 2017 is Rp. 11,574.71 andthe cost of production per ton oflime stone after analyzed isRp. 10.349,08 so that companies can reduce the production costs amounted to 10.58%.